Integrated knowledge and information audit: a case study - González Guitián, María Virginia; de Zayas Pérez, María Rosa; Martínez Ríos, Marcos Antonio (Revista General de Información y Documentación, 2016)
In this paper the results of the application of an integrated audit methodology of information and knowledge carried out in a Research Center of the Ministry of Science Technology and Environment of the province of Holguín, Cuba, are presented. This methodology consists of seven stages with a hybrid approach directed to review the strategy and policy of information and knowledge management, identify, make inventory and map the resources of I+K and their flows, and evaluate the processes associated with its management. Top management specialists and researchers of this center, demonstrated the effectiveness of the methodology applied, whose results led to realign the strategic projection in relation to the I+K management, redesign the information flows of key processes, have a directory of experts by areas and plan the future learning and professional development.
Keywords: information audit; knowledge audit; knowledge management information; management knowledge; I K audit